2008
DOI: 10.1111/j.1468-0106.2007.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Regional Exchange Rate Regime in East Asia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 6 publications
1
43
0
Order By: Relevance
“…However, the yen quickly peaked following stagnation of the Japanese economy. In the aftermath of the Asian financial crisis, there was an important proposal for creating an Asian currency (Kawai 2008). This proposal, however, lost momentum as its role model, the eurozone, fell into a debt crisis.…”
Section: What Are the Likely Implications?mentioning
confidence: 99%
“…However, the yen quickly peaked following stagnation of the Japanese economy. In the aftermath of the Asian financial crisis, there was an important proposal for creating an Asian currency (Kawai 2008). This proposal, however, lost momentum as its role model, the eurozone, fell into a debt crisis.…”
Section: What Are the Likely Implications?mentioning
confidence: 99%
“…Following Franken and Wei (1992), both Ogawa and Shimitzu (2005) and Kawai (2007) regressed special-drawing-right (SDR) exchange rate returns of the domestic currency on the returns of the US dollar, yen, and euro visa-vis the SDR, and showed the resilience of the US dollar peg in the East Asian countries up to the mid-2000s. A similar conclusion was reached by Hernandez and Montiel (2003) by employing the relative volatilities of exchange market pressure indices.…”
Section: Introductionmentioning
confidence: 99%
“…McKinnon and Schnabl (2004) coined the phrase, "the resurrection of an East Asian dollar-standard," a finding that was corroborated by Benassy-Quere and Coeure (2006). Somewhat different evidence was provided, however, by Kawai (2008) who found that, with the exception of a few US dollar peg economies in the East Asian region such as the PRC and Hong Kong, China, most East Asian currencies began to exhibit greater exchange rate flexibility a few years after the Asian financial crisis, and some currencies adopted currency basket systems in which the yen played an important part.…”
mentioning
confidence: 81%